Magnetic Nanoplatelet‐Based Spin Memory Device Operating at Ambient Temperatures. Issue 17 (3rd March 2017) - Koplovitz, Guy; Primc, Darinka; Ben Dor, Oren; Yochelis, Shira; Rotem, Dvir; Porath, Danny; Paltiel, Yossi
Abstract : There is an increasing demand for realizing a simple Si based universal memory device working at ambient temperatures. In principle, nonvolatile magnetic memory can operate at low power consumption and high frequencies. However, in order to compete with existing memory technology, size reduction and simplification of the used material systems are essential. In this work, the chiral‐induced spin selectivity effect is used along with 30–50 nm ferromagnetic nanoplatelets in order to realize a simple magnetic memory device. The vertical memory is Si compatible, easy to fabricate, and in principle can be scaled down to a single nanoparticle size. Results show clear dual magnetization behavior with threefold enhancement between the one and zero states. The magnetization of the device is accompanied with large avalanche like noise that is ascribed to the redistribution of current densities due to spin accumulation inducing coupling effects between the different nanoplatelets. Abstract : Magnetic nanoplatelets are used as memory bits at ambient conditions . Using the chiral‐induced spin selectivity effect to generate spin‐polarized current, the magnetization state is controlled without a permanent magnet. The results show a threefold ratio between the one and zero states. This technology is simple, utilizes low currents, and allows miniaturization to a scale of ≈30 nm.